Epigallocatechin-3-gallate protects against hepatic ischaemia–reperfusion injury by reducing oxidative stress and apoptotic cell death. (December 2016) - Tak, Eunyoung; Park, Gil-Chun; Kim, Seok-Hwan; Jun, Dae Young; Lee, Jooyoung; Hwang, Shin; Song, Gi-Won; Lee, Sung-Gyu
Objective: To investigate the protective effects of epigallocatechin-3-gallate (EGCG), a major polyphenol source in green tea, against hepatic ischaemia–reperfusion injury in mice. Methods: The partial hepatic ischaemia–reperfusion injury model was created by employing the hanging-weight method in C57BL/6 male mice. EGCG (50 mg/kg) was administered via an intraperitoneal injection 45 min before performing the reperfusion. A number of markers of inflammation, oxidative stress, apoptosis and liver injury were measured after the ischaemia–reperfusion injury had been induced. Results: The treatment groups were: sham-operated (Sham, n  = 10), hepatic ischaemia–reperfusion injury (IR, n  = 10), and EGCG with ischaemia–reperfusion injury (EGCG-treated IR, n  = 10). Hepatic ischaemia–reperfusion injury increased the levels of biochemical and histological markers of liver injury, increased the levels of malondialdehyde, reduced the glutathione/oxidized glutathione ratio, increased the levels of oxidative stress and lipid peroxidation markers, decreased B-cell lymphoma 2 levels, and increased the levels of Bax, cytochrome c, cleaved caspase-3, and cleaved caspase-9. Pretreatment with EGCG ameliorated all of these changes. Conclusion: The antioxidant and antiapoptotic effects of EGCG protected against hepatic ischaemia–reperfusion injury in mice.